Teaching the basics of Life Safety according to the specifics of the subject of educational material - I. G. Kretova; O. V. Belyaeva; Е. А. Koscova (Вестник Самарского университета: История, педагогика, филология)
The authors studied possibilities of using modern technologies in the process of teaching the discipline «Fundamentals of health and safety», identified specific factors for optimizing the mastery of the discipline in higher education in the context of digitalization of education. 339 students from the 1st to the 4th year of education who finished the study of «health and safety» and «Fundamentals of health and safety» in autumn semester of 2023–2024 were polled with the usage of Google Disc questionnaire. Student`s attendance of classes, results of student`s assessment of organizing of educational process were analyzed by authors. Authors revealed the difference in perception of information by students of the 1st educational year and students of 3rd and 4th educational year. It must be taken into account when choosing teaching methods and technologies. All students agree that practical classes of «Fundamentals of health and safety» should be held offline and give preference to having tasks in mini-groups. The vast majority notes the insufficient number of classes for studying the discipline. Periodic monitoring of the quality of education, considering student`s surveys helps in time to identify difficulties in students’ mastery of the material and carry out corrective measures not only in the educational process, but also directly in the classroom. The universality of the disciplines of «health and safety» and «Fundamentals of health and safety» allows to use effectively modern technologies, including digital ones in the process of teaching in higher education, considering the specifics of the subject matter of the material being studied.